(RESPONSE OF BEET TO DOSES OF POTASSIUM) (IN OXISOL WITH HIGH CONTENT OF THE NUTRIENT) - Cardoso Passos, Danilo Dos Reis [UNESP] (2020)
Fertiliser recommendation tables for beet culture have been prepared based on the response to potassium (K) doses in soils with a low nutrient content. However, there is little research that evaluates potassium fertilisation for beet crops in soil with high K content, a condition commonly found, which allows a better understanding of the crop's response to the nutrient. The objective was to evaluate the response of beet to doses of K in Oxisol with a high K content. The experiment was carried out in the field, with an experimental design in randomised blocks, in a 4 x 2 factor scheme with four replications. The doses of K were 0, 60. 120 and 180 kg ha(-1) of K2O, and the cultivars were 'Early Wonder' and 'Kestrel'. At 50 days after transplantation, the levels of nitrogen (N), phosphorus (P), K and boron (B) in the diagnostic leaf were evaluated. Beet yield and accumulation of these four nutrients were analysed at harvest. The doses of K positively influenced the leaf content of K; however, without an effect on beet yield. Therefore, in Oxisol with a high K content available, potassium fertilisation is not recommended. To maintain soil fertility at a high potassium content, fertilisation with 162 and 126 kg ha(-1) of K2O is recommended for 'Early Wonder' and 'Kestrel', respectively: doses equivalent to the quantities exported by the beet root.